Sumur Resapan sebagai Alternatif Drainase Berwawasan Lingkungan untuk Penanggulangan Genangan Banjir di Desa Suwangi Timur Kabupaten Lombok Timur - Budianto, Muh Bagus; Saidah, Humairo; Negara, IDG Jaya; Setiawan, Ery; Supriyadi, Anid (Jurnal Gema Ngabdi, 2024)
East Suwangi Village is one of the villages in Sakra District, has an area of ​​2.17 km2, has hilly geographical conditions and a population of 5,069 people. Based on survey results and interviews with village heads, some areas are prone to flood disasters. The flooding that occurred was caused by overflow from drainage channels, causing it to accumulate on roads and residential areas. One effort to minimize inudation is the implementation of an environmentally friendly drainage system by constructing infiltration wells along flooded channels. The method used in this community service activity is to explain environmentally friendly drainage systems to the community and the practice of making infiltration wells in locations that are often flooded. The result of this activity is an increase in public understanding of the function and benefits of infiltration wells as a medium for environmentally friendly flood management. And the public can see firsthand how to make infiltration wells through practice in locations that are often flooded.